PENERAPAN METODE MOORA DALAM PENGAMBILAN KEPUTUSAN PENERIMA BANTUAN SOSIAL - Kiki Kusumawati; Ridwan Faisal Rizki (FAKULTAS TEKNIK, 2025)
The provision of humanitarian social assistance is given to human society are in a state of instability, one of which is in a condition of economic and social crisis. Humanitarian social assistance can also be channeled or delivered through the management of non-governmental organizations that have the same role in protecting the community from various conditions of social risk. Problems that are often faced by the manager of the Solidarity Insan Peduli (SIP) Foundation, where is difficult for decision makers of determine who will be prioritized for assistance in accordance with the specified requirements. So that sometimes there is an attitude of subjectivity towards decision making determined by the leadership. The goal to be achieved is decision making in selecting recipients of humanitarian social assistance according to objective criteria. To solve the problem with the Multi Objective Optimization on the basis of Ratio Analysis Method (MOORA) is applied. The results achieved at the research are the ability to apply the MOORA method in decision making to select recipients of humanitarian social assistance in accordance with objective and targeted criteria.